2022
DOI: 10.18231/j.ijcbr.2021.055
|View full text |Cite
|
Sign up to set email alerts
|

Sigma metrics in quality control- An innovative tool

Abstract: The clinical laboratory in today’s world is a rapidly evolving field which faces a constant pressure to produce quick and reliable results. Sigma metric is a new tool which helps to reduce process variability, quantitate the approximate number of analytical errors, and evaluate and guide for better quality control (QC) practices.To analyze sigma metrics of 16 biochemistry analytes using ERBA XL 200 Biochemistry analyzer, interpret parameter performance, compare analyzer performance with other Middle East studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Values for TEa were extracted from RIQAS SOTA 2021 and CLIA 2024. As indicated in Tables 1, 2, the performance of the analytes was graded into six categories based on the sigma level: world-class (sigma ≥ 6), excellent (5 ≤ sigma < 6), good (4 ≤ sigma < 5), marginal (3 ≤ sigma < 4), poor (2 ≤ sigma < 3), and unacceptable (sigma < 2) [12]. Table 3 shows the sigma values in terms of six grades and the analytes falling under those categories for both level 1 and level 2 IQC data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values for TEa were extracted from RIQAS SOTA 2021 and CLIA 2024. As indicated in Tables 1, 2, the performance of the analytes was graded into six categories based on the sigma level: world-class (sigma ≥ 6), excellent (5 ≤ sigma < 6), good (4 ≤ sigma < 5), marginal (3 ≤ sigma < 4), poor (2 ≤ sigma < 3), and unacceptable (sigma < 2) [12]. Table 3 shows the sigma values in terms of six grades and the analytes falling under those categories for both level 1 and level 2 IQC data.…”
Section: Resultsmentioning
confidence: 99%
“…Analytes were categorized as world-class, excellent, good, marginal, poor, and unacceptable based on their sigma values. The integration of Six Sigma methodology into clinical biochemistry laboratories has been extensively explored in previous studies [ 11 , 12 ]. The review by Westgard et al demonstrated that Six Sigma metrics provide a robust framework to analyze laboratory errors and optimize the QC rules as per the performance of the laboratory tests [ 14 ].…”
Section: Discussionmentioning
confidence: 99%